2015
DOI: 10.3892/mmr.2015.4618
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Th17 and nTreg cell frequencies and the stages of progression in chronic hepatitis B

Abstract: Several studies have suggested that the balance of T helper 17 (Th17) and natural regulatory T (nTreg) cells in the Th17‑mediated immune response are critical in the pathogenesis of viral hepatitis. The aim of the present study was to examine the role of circulating Th17 and nTreg cells in the disease progression of hepatitis B virus (HBV) infection. A total of 40 patients with chronic HBV (CHB), 27 patients with HBV‑associated cirrhosis, 20 patients with HBV‑associated liver failure and 20 healthy controls we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
8
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 41 publications
6
8
0
1
Order By: Relevance
“…5 Previous works demonstrate increased IL-17 expression and circulating type 17 helper T cells in HBV-linked and HCV-linked liver fibrosis. [38][39][40][41] Our findings reinforce these works (Fig. 2).…”
Section: Innate Immunity In Hepatitis B and Dsupporting
confidence: 91%
“…5 Previous works demonstrate increased IL-17 expression and circulating type 17 helper T cells in HBV-linked and HCV-linked liver fibrosis. [38][39][40][41] Our findings reinforce these works (Fig. 2).…”
Section: Innate Immunity In Hepatitis B and Dsupporting
confidence: 91%
“…To our knowledge, only five patients with HBV infection have been treated so far with secukinumab and, similarly to our case, HBV reactivation or elevation in liver enzymes was not found [24,25]. In this regard, several studies have shown that Th17 cells play a critical role in the pathogenesis of viral hepatitis, with serum levels of IL-17 being able to predict the severity of liver damage and fibrosis [26]. For this reason, inhibitors of IL-17 as secukinumab could have a protective role in the progression of liver injury and may be preferred in psoriatic patients with HBV or HCV infection.…”
Section: Discussionsupporting
confidence: 75%
“…These results are consistent with all previous data indicating the high proportion of Th17 cells among PBMCs of patients with HBV infection 24 . Furthermore, Th17 might also be linked to continuous HBV infection 25 . The Treg/Th17 balance, the Th17/IL‐17 axis, IL22 and IL23, etc., have been considered the key prognostic and immunopathological elements in patients with HBV.…”
Section: Discussionsupporting
confidence: 92%